Biologic Therapy in Head and Neck Cancer: A Road with Hurdles. (13th June 2012) - Specenier, Pol; Vermorken, Jan B.
Abstract : The epidermal growth factor receptor (EGFR) is overexpressed in the vast majority of cases of squamous cell carcinoma of the head and neck (SCCHN). A high EGFR expression is associated with an unfavorable prognosis. Cetuximab is a chimeric human/murine IgG1 antibody which binds with high affinity to the EGFR. It is the only targeted agent which got approval for the treatment of SCCHN from the regulatory agencies of Europe and the United States, both in locoregionally advanced disease, in association with radiation, and in recurrent/metastatic disease. The outcome of trials involving other EGFR-directed monoclonal antibodies, that is, zalutumumab and panitumumab, was consistent with the results with cetuximab. However these trials failed to meet their primary endpoint. The results with EGFR-directed tyrosine kinase inhibitors have been disappointing. Other potential targets for treatment in SCCHN include the entire ErbB family, the vascular endothelial growth factor (VEGF) and its receptor (VEGFR), the insulin-like growth factor 1 receptor (IGF-1R), the insulin receptor (IR), histone deacetylases (HDAC), the mammalian target of rapamycin (mTOR), the platelet-derived growth factor receptor (PDGFR), heat-shock protein 90 (HSP90), nuclear factor-kappa B (NF-κB), aurora A or B, and phosphatidylinositol 3-kinase (PIK3CA).